Pengaruh Profitabilitas, Leverage dan Ukuran Perusahaan terhadap Nilai Perusahaan pada Perusahaan Manufaktur Sub Sektor Food dan Beverage yang terdaftar di Bursa Efek Indonesia Periode 2016-2020 - Piasti, Trianita; Suswandoyo, M. Imam (LPPM STIE PPI, 2022)
Introduction/Main Objectives: To determine the effect of profitability, leverage and company size on firm value in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. Background Problems: A sense of trust from other investors, so that many investors will sell their shares back and the company's capital will certainly decrease and it will be difficult to carry out company operations. Novelty: Re-examining the existing model with a different sector, namely the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020. Research Methods: Using quantitative methods with secondary data types in the form of financial reports and analytical techniques used by the SPSS analysis tool. Findings/Results: Underpricing Reputation (RU) and Percentage of shares offered affect underpricing at the time of IPO. Conclusion: Partially, profitability has a significant effect on firm value, leverage has no significant effect on firm value, firm size has no significant effect on firm value, and simultaneously profitability, leverage and firm size have a significant effect on firm value.